2012
DOI: 10.1016/j.bbamem.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol dependence of Newcastle Disease Virus entry

Abstract: Lipid rafts are membrane microdomains enriched in cholesterol, sphingolipids, and glycolipids that have been implicated in many biological processes. Since cholesterol is known to play a key role in the entry of some other viruses, we investigated the role of cholesterol and lipid rafts in the host cell plasma membrane in Newcastle Disease Virus (NDV) entry. We used methyl-β-cyclodextrin (MβCD) to deplete cellular cholesterol and disrupt lipid rafts. Our results show that the removal of cellular cholesterol pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 66 publications
(92 reference statements)
0
26
0
2
Order By: Relevance
“…Similarly, the activity of PKC is essential for the entry of different non-enveloped [39] or enveloped viruses, such as influenza virus [38], alphavirus, rhabdovirus, poxvirus and herpes virus [40], which has been related to the entry through receptor-mediated endocytosis. Furthermore, we have previously suggested that caveolae/rafts could be a possible platform for NDV entry [28,41] and caveolae seem to be the major cell surface locations for PKC [42,43]. We also analyzed the effect of dynasore, a drug that inhibits the GTPase activity of dynamin 1, which has been implicated in clathrinand caveola-mediated endocytosis [44].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the activity of PKC is essential for the entry of different non-enveloped [39] or enveloped viruses, such as influenza virus [38], alphavirus, rhabdovirus, poxvirus and herpes virus [40], which has been related to the entry through receptor-mediated endocytosis. Furthermore, we have previously suggested that caveolae/rafts could be a possible platform for NDV entry [28,41] and caveolae seem to be the major cell surface locations for PKC [42,43]. We also analyzed the effect of dynasore, a drug that inhibits the GTPase activity of dynamin 1, which has been implicated in clathrinand caveola-mediated endocytosis [44].…”
Section: Resultsmentioning
confidence: 99%
“…Cholesterol-enriched medium (CHEM) was prepared as described previously (37,38). Briefly, 10 mM cholesterol (CH) (Santa Cruz Biotechnology) stock was prepared in stirred and warmed DMSO at 80°C on a heating block.…”
Section: Methodsmentioning
confidence: 99%
“…Cantín et al [64] described the colocalization of NDV with caveolin and with the early endosome marker EEA1, leading to the suggestion that a certain percentage of the virus manages to penetrate the cell through caveolin-dependent endocytic pathways [67]. In that particular study, after 30 minutes of NDV infection, a strong colocalization of NDV HN protein and EEA1 was found, thus confirming that HN is targeted to early endosomes.…”
Section: Ndv-rac1 Interaction For Proliferation and Invasion Inhibmentioning
confidence: 76%